The known genetic variants of BRCA1, BRCA2 and NOD2 in pancreatitis and pancreatic cancer risk assessment - Jarosław Matykiewicz; Wioletta Adamus-Białek; Monika Wawszczak-Kasza; Bartosz Molasy; Magdalena Kołomańska; Rusłan Oblap; Łukasz Madej; Dorota Kozieł; Stanisław Głuszek (Scientific Reports)
Abstract The single nucleotide polymorphism in NOD2 (rs2066847) is associated with conditions that may predispose to the development of gastrointestinal disorders, as well as the known BRCA1 and BRCA2 variants classified as risk factors in many cancers. In our study, we analyzed these variants in a group of patients with pancreatitis and pancreatic cancer to clarify their role in pancreatic disease development. The DNA was isolated from whole blood samples of 553 patients with pancreatitis, 83 patients with pancreatic cancer, 44 cases of other pancreatic diseases, and 116 healthy volunteers. The NOD2 (rs2066847), BRCA1 (rs80357914) and BRCA2 (rs276174813) were genotyped. The statistically significant 3-fold increased risk of pancreatic cancer was detected among the patients with rs2066847 polymorphism (OR = 2.77, p-value = 0.019). We did not find the studied polymorphisms in BRCA1 (rs80357914) and BRCA2 (rs276174813). However, the adjacent polymorphisms have been detected only in patients with pancreatic diseases. The studied variant in NOD2 occurs more frequently in pancreatic patients and significantly increases the risk of pancreatic cancer. It can be considered as a genetic risk factor that predisposes to cancer development. The analyzed regions in BRCA1 and BRCA2 may be a potential target in further search for a genetic marker of pancreatic diseases.